PENGUATAN KEDUDUKAN NORMATIF PERATURAN PRESIDEN DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN INDONESIA: UPAYA MEWUJUDKAN KEPASTIAN HUKUM DAN SIMPLIFIKASI REGULASI - Mudhafar Anzari; Abdul Gani Haitamy; Al Manar; Zulfa Zainuddin (CV. Lafadz Jaya, 2026)
This study aims to analyze the normative status of Presidential Regulations (Perpres) within the Indonesian legal system and to examine the urgency of strengthening their role in achieving legal certainty and regulatory simplification. The study employs a normative legal research method using a legislative approach, a conceptual approach, and a case study approach. The legal materials utilized consist of primary, secondary, and tertiary sources, which are qualitatively analyzed through legal interpretation techniques and legal reasoning. The research results indicate that Presidential Regulations hold a strategic position within the hierarchy of legislation because they derive from the President’s constitutional authority as the holder of executive power under Article 4(1) of the 1945 Constitution of the Republic of Indonesia. However, the phenomenon of regulatory obesity, characterized by the proliferation of Ministerial Regulations, has led to regulatory fragmentation, disharmony of norms, and a reduction in legal certainty. Based on Hans Kelsen’s theory of the hierarchy of norms, Hans Nawiasky’s theory of the structure of norms, Gustav Radbruch’s concept of legal certainty, and Philipus M. Hadjon’s theory of authority, this study argues that strengthening Presidential Regulations is necessary to clarify the hierarchical relationships among regulations, enhance policy harmonization, and strengthen government coordination. This study proposes a model for strengthening Presidential Regulations through reinforcing hierarchical functions, limiting Ministerial Regulations to technical aspects, and optimizing regulatory harmonization mechanisms. This model is expected to support regulatory reform, enhance legal certainty, and achieve effective, coordinated, and accountable governance.